Integrated Individual Service with Community Approach in Therapeutic Community-based Rehabilitation at Lido Rehabilitation Centre of the Indonesian National Narcotics Agency (Faculty of Social Science, Universitas Negeri Semarang, 2020)
Recovery process of substance use disorders requires comprehensive approach. The Indonesian National Narcotics Agency (Badan Narkotika Nasional/BNN) provides Therapeutic Community (TC) rehabilitation service. TC approach is about community that faces common issue, gather together to support each other to overcome the issue. Although TC program uses community approach, it is not yet accommodating clientâ€™s needs. For that, BNN developed an integrated individual service through community approach called â€œMoving Classâ€. Moving class is not a new approach. It is widely used in basic education, where students are moving out from their class and actively seeking a particular and designated class with particular topic, according to the schedule.Â Â Moving class in this context is modeling same approach. Standard approach provided knowledge and information sessions related to addiction through classical, where facilitator come to the class full of clients. and delivers the subject. While moving class ask clients to determine their own topic based on their own needs and ask client to find out the venue of its topic. So client have to actively move from spot to spot. They also need to make an adjustment to each class, both to the facilitator and their peer in the same class. As BNNâ€™s mission is to provide evidence-based services, there is need to do systematic review to clinically assess â€œMoving Classâ€ method. The study question is whether Moving Class method offers better behavioral changes in recovery process compared to the standard TC. This study used mixed method approach with quasi experimental design, whereby 34 participants in intervention arm received Moving Class intervention and 43 participants in standard of care (SOC) arm received standard TC. We used instruments like Client Evaluation of Self Treatment of Texas Christian University and Change Assessment Scale of University of Rhode Island to evaluate the behavioral changes. Results showed that participants in intervention arm experienced inclination to receive treatment, more participation in rehabilitation process, maintained good relationship in counseling, were able to identify problems. Also, the number of participants had had mental health issues during treatment declined. This study proved that Moving Class method provided improved behavioral changes compared to the classical one.